The Study of the Groundwater Problem Is Particularly Relevant in the Alwar Region: Addressing the Challenges of Groundwater Management in the Alwar Region (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Water covers all aspects of life. Access to clean water and sanitation can quickly turn problems into power - empower people during school and work, and contribute to improving the lives of women, children and families around the world. water has emerged as a strategically important resource due to its growing demand for agriculture, domestic and industrial use. its adequate and adequate provision is essential to provide stability in food production and social independence. Increased demand for water has encouraged the development of groundwater supply. Various development projects over the years have adversely affected the state of the groundwater system in government. There is a need for scientific planning in groundwater construction under a different hydrogeological environment and to change the effective methods of public participation in better groundwater management. groundwater systems, which will help meet the shortage of drinking water, improve irrigation facilities and stabilize water resources in the province.